(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
Neologism, as a dynamic linguistic phenomenon, plays a fundamental role in language development and adaptation. This study explores the definition, classification, and theoretical underpinnings of neologisms within the field of linguistics. It analyzes the causes and functions of neologisms, their typology, and their impact on contemporary language use. The paper also discusses various linguistic theories that explain the emergence and integration of neologisms into the lexicon. By addressing both structural and sociocultural perspectives, this article aims to provide a comprehensive understanding of the phenomenon of neologism.